Cada poema já sonha outra forma: Poesia e poética cinematográfica em Carlos de Oliveira e Manuel Gusmão - Patrícia Resende Pereira (2018)
In this present thesis, it is studied the cinematograph rereading proposed by the critic and poet Manuel Gusmão when writting the script of Carlos de Oliveira Sobre o lado esquerdo (2007), directed by Margarida Gil. It is realized by Manuel Gusmão, a well knowm poet and critic that widely studied the work of Gândaras author, an attempt to expand cinematography and poetically the authors Carlos de Oliveira work. But not only, once its possible to notice, specially on A terceira mão (2008), an attempt of thinking, and sometimes solve some of centrals aspects of Carlos de Oliveiras poetic work. For this purpose, this research concentrates in the concept of dialogism, because is noticeable in the Manuel Gusmãos poetry and academic work, as it proves his books title: Uma razão dialógica (2011). Furthermore, its relevant to know that Carlos de Oliveiras poetry concept also concentrate on dialogism idea, specially on O aprendiz de feiticeiro (1971). Its important to keep in mind that, to write the script, Manuel Gusmão uses the concept of collage, same resource as Carlos de Oliveira to compose some of his texts. For the movies script, Manuel Gusmão proposes a collage with fragments of Carlos de Oliveiras work. For this, the essayist finds in Finisterra: paisagem e povoamento the movies heart, since, in order to constitute a narrative, this is the book that provides the characters. From this union of fragments, weve got the possibility of an expansion of Carlos de Oliveiras work by Manuel Gusmãos hands, in a way, to use the ideia of Lavoisier, from Sobre o lado esquerdo (1968), to put in practice the proposal of: every poem, / in its uncertain / calligraphic profile, / is already dreaming / of another form1 (OLIVEIRA, 2004b, p. 53).